2010
DOI: 10.1177/0886260510368154
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Pregnancy and Intimate Partner Violence Before and During Pregnancy Among Latina Women in Los Angeles, California

Abstract: The purpose of this paper was to examine the relationship between unintended pregnancy and intimate partner violence (IPV) before and during pregnancy among Latinas. A cross-sectional interview measuring pregnancy intent, IPV, and acculturation, using the Acculturation Rating Scale for Mexican Americans (ARSMA-II), was conducted among Latina women in their 2(nd) or 3(rd) trimester of pregnancy at clinics in Los Angeles (n = 313). Overall, 44% of women reported an unintended pregnancy. The prevalence of physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 44 publications
6
31
0
4
Order By: Relevance
“…With regard to obstetric characteristics of the participants and the association with the occurrence of IPV during pregnancy, there was a statistically significant result between the occurrence of violence and desire of pregnancy, and women who did not desire the pregnancy had 4.3 times more chances of suffering violence compared to those who desired the pregnancy, confirming the findings of other studies (13)(14) .…”
Section: Discussionsupporting
confidence: 82%
“…With regard to obstetric characteristics of the participants and the association with the occurrence of IPV during pregnancy, there was a statistically significant result between the occurrence of violence and desire of pregnancy, and women who did not desire the pregnancy had 4.3 times more chances of suffering violence compared to those who desired the pregnancy, confirming the findings of other studies (13)(14) .…”
Section: Discussionsupporting
confidence: 82%
“…62 In a quantitative study, when an unintended pregnancy occurred among less acculturated Latinas, it was associated with greater risk of physical IPV during pregnancy (unadjusted OR 2.57; 95% CI: 1.06-6.23). 60 Associations with unexplained menstrual irregularity were strongest among African American women when compared to other groups (i.e., European American, Latina, and other ethnic groups). 59 Related to the association between IPV and HIV risk, multiple studies have found that African American and Latina women with lifetime and recent experiences of IPV are more likely to report multiple sex partners, partner-related risk (i.e., having a partner who has multiple or concurrent sex partners, is HIV-infected, injects drugs, and/or has an STI), inconsistent condom use, and an STI or STI-related symptoms when compared to African American and Latina women with no experiences of IPV.…”
Section: Mental Healthmentioning
confidence: 95%
“…), which may not be as important in understanding parental beliefs as more cognitive measures of acculturation. The ARSMA-II has been used most often in studies of health behavior and has been associated with variables, such as physical activity and problem-solving in a diabetes intervention (Barrera, Toobert, Strycker, & Osuna, 2011) and the rate of unplanned pregnancy among Latina women (Martin & Garcia, 2011). Thus, it is possible that it may be a more appropriate measure in predicting behavioral outcomes, rather than more cognitive outcomes, such as etiological beliefs as in the current study.…”
Section: Acculturation and Etiological Beliefsmentioning
confidence: 81%